A theoretical investigation on the selective extraction of Cu(II) from Ni(II) by 2-aminomethylpyridine derivatives: A DFT study. (1st January 2019) - Qiu, Xuejing; Hu, Huiping; Yang, Jinpeng; Cheng, Zeying; Ji, GuangFu
Graphical abstract: Theoretical investigation on the selective extraction of Cu(II) from Ni(II) with 2-aminomethylpyridine derivatives by DFT provides insight into the possible complexation reactions and the order of Cu(II)/Ni(II) selectivity for these four ligands in solution, which were helpful to design the novel selective ligands for efficient separation of specific metal ions. Abstract: The structures of Cu(II) and Ni(II) extraction complexes with 2-aminomethylpyridine derivatives including N-octyl-2-aminomethylpyridine (AMPH), N, N-dioctyl-2-aminomethylpyridine (AMPO), tert-butyl 2-(N-octyl-2-picolyamino)acetate (AMPA), and tert-butyl 2-[N-(tert-butyloxycarbonylmethyl)-2-picolyamino]acetate (AMPY) have been investigated by density functional theory (DFT). The optimized geometries of the Cu(II) complexes in the gas phase and in solution are in accordance with the crystallographically data. The significant transfer of electrons from ligands to metal ions was found during the formation of the complexes, and the metal–ligand interactions for all the extraction complexes are mainly ionic. The changes in the calculated Gibbs free energies of the extractions indicated that AMPH, AMPO, AMPA, and AMPY prefer to be coordinated with Cu(II) than with Ni(II) and that the order of Cu(II)/Ni(II) selectivity for these four ligands in solution is AMPA > AMPO > AMPH > AMPY, which was in agreement with the experimental results. That is to say, both the conversion of aminomethyl groups from secondary amines to tertiary amines and the introduction of a carbonyl oxygen on the ester group have an obvious influence on the selectivity of the ligands. For the ligands AMPH, AMPO and AMPA, the participation of the coordination of water molecules is not conducive to the stability of the metal complexes and the selectivity of these ligands. Moreover, the stable species of Cu(II) complexes with AMPO and AMPA in the extraction processes were correspondingly [Cu(AMPO)Cl2 ]2 and [Cu(AMPA)Cl2 ], which was consistent with the stable species of Cu(II) observed by the electrospray mass spectrometry (ESI-MS) in our previous work.